Characterization of stress field evolution during 3D internal fracture propagation using additively printed models and frozen stress techniques. (February 2021) - Ju, Yang; Liu, Peng; Ren, Zhangyu; Mao, Lingtao; Chiang, Fu-pen
Highlights: A method to quantify the stress field of a 3D internal crack is presented. Method captures and describes the 3D rabbit-ear crack propagation trajectory. Characteristics of the full-field stress of spatial crack trajectory are analyzed. Constraining forces cause arrest of the wing crack and leads to mode III failure. Abstract: The characteristics of full-field stress govern internal crack initiation and propagation in solids. It is challenging to use traditional fracture theories to quantify three-dimensional (3D) full-field stress evolution during internal crack propagation because the propagation trajectory appears as a complex spatial surface. This complexity also causes difficulty in choosing the fracture criteria for materials when numerically predicting crack propagation in solids. A visualization method to directly reveal and quantify the evolution of the stress field associated with the 3D initiation and propagation of a single embedded crack using additively printed models and frozen stress techniques is introduced. The results show that the proposed method can capture the 3D rabbit-ear crack propagation trajectory and characterize the associated full-field stress evolution. The findings explain the mechanism and governing factors of the 3D internal rabbit-ear crack propagation. This study provides a method to quantify the hidden stress field that governs 3D internal crack propagation, thereby serving as an experimental basis for developing 3D fracture mechanics of materials.